Characteristics associated with the adoption of consumer-based -self-sampling methods for sexually transmitted infection screening. - Griner, Stacey B.; Beckstead, Jason W.; Vamos, Cheryl A.; Puccio, Joseph A.; Perrin, Kay; Daley, Ellen M. (Journal of American College Health, 2024)
Objective: To identify theory-based innovation characteristics associated with the adoption of consumer-based self-sampling methods for sexually transmitted infection screening. Participants: Guided by the Diffusion of Innovation, survey data from people assigned female at birth (AFAB) (n = 92) were analyzed. Methods: Forward regression models and a path analysis were used to predict adoption by characteristics, using maximum likelihood estimation. Measures included acceptability, comfort, addresses healthcare needs, willingness to adopt self-sampling methods, and innovation characteristics. Results: Predictors of willingness to adopt were no clinic visit (relative advantage), convenient pick-up (relative advantage), and low cost. Variables with direct effects on adoption included: addresses healthcare needs, comfort, acceptability, and no clinic visit. Conclusions: Relative advantage was a salient factor and prioritizing this construct in intervention development may facilitate adoption. Results can guide the development of an innovative, theory-based intervention that promotes adoption of self-sampling methods, ultimately improving STI screening rates.